Evaluation of dumpsites in Lattakia and the possibility of rehabilitation - حلوم, علا; هيثم شاهين,; نسرين خلوف , (Latakia University Journal -Engineering Sciences Series, 2023)
The rapid development of human societies has led to high population density, and expansion of agricultural, economic, industrial and commercial activities, which increased the amount of solid waste and spread of random dumps. This became a serious environmental problem. This research is aimed at evaluating the rehabilitation potential and the risk level of Al-Bassa dumpsite, because it is located close to the city also it is the main dumpsite in Lattakia, by developing a computer program based on the Integrated Risk-Based Approach (IRBA), which was calculated from the addition of the sensitivity Index output with the attribute weightage of the (27) parameters related to site, waste and infiltration. A total risk index of (709) was obtained for Al-Bassa dumpsite, indicating high risk evaluation and need to close and rehabilitate the dumpsite. Questionnaires distributed to dwellers around the dumpsite also showed that (68%) of those interviewed do not agree with the present management of the dumpsite, and they emphasized the negative effects of the dumpsite on the surroundings and asked for its rehabilitation. A method of rehabilitation was proposed in two stages: the first is the aerobic biological treatment of the buried waste for a period of six months, as most of the waste is organic, then an adjustment layer for collecting gases and layers of insulation and protection are installed in order to turn it into a green area, and then planting trees and shrubs with deep roots.